On Some New Generalized Difference Statistically Convergent Sequence Spaces Defined by a Sequence of Orlicz Functions - Bektas, Ciadem Asma; Atici, Gulcan (Kyungpook Natl Univ, Dept Mathematics, 2010)
In this paper we introduce the new generalized difference sequence spaces l(infinity) (Delta(n)(upsilon),M,p,q,s), (c) over bar (Delta(n)(upsilon),M,p,q,s), (c(0)) over bar, M,p,q,s), m(Delta(n)(upsilon),M,p,q,s) and m(0)(Delta(upsilon)n,M,p,q,s) defined over a seminormed sequence space (X, q). We study some of its properties, like completeness, solidity, symmetricity etc. We obtain some relations between these spaces as well as prove some inclusion result.
Keywords: Difference sequence spaces; statistical convergence; seminorm